Economic benefits of mass sport events - Gureeva, E. A.; Skryl, T. V.; Sukhanovsky, Y. A.; Askarov, A. D. (Theory and Practice of Physical Culture, 2017)
In the context of the modern economic and political challenges, and the increasing numbers of study reports exploring the ways to improve the efficiency of mass sport events on the whole and ethnic events in particular a top priority is being given to the issues of economic benefits of mass sport events. Objective of the study was to analyse the importance of mass sport events for host communities and their willingness to finance the events from the communal or individual funds. The study was based on the data of the Russian survey initiated and sponsored by the Federation of Traditional Festivals and Ethnic Sports of Russia, a Russian Non-governmental Organisation with a research support provided by G.V. Plekhanov Russian University of Economics. Subject to a representative sample under the study were 23 regions of the RF. The study data was indicative of the mass sport events being beneficial as verified by a variety of criteria including the host region`s image improvement; protection of the cultural and historic traditions; and the growing attractiveness of the host region for tourists. It was the personal competitive and valuable socialising experience that was found the key motivator for participation of the local communities in the traditional games and festivals. Having analysed the outcome data of the survey, we categorised the regions into five WTP (willingness to pay) categories. Furthermore, the study produced a classified account of the average income generated by the mass sport events versus the average revenues from the traditional match-days. The study findings gave the grounds for the authors to highlight the most promising avenues for the mass sport events hosting projects.